A single mediaprocessor-based programmable ultrasound system. - Sikdar, S. (IEEE Transactions on information technology in biomedicine)
We have developed a programmable ultrasound imaging system using a single commercially available mediaprocessor. We have efficiently mapped all of the necessary B-mode processing algorithms on the underlying processor architecture, including envelope detection, dynamic range compression, lateral and axial filtering, persistence processing, and scan conversion. Our system can handle varying specifications ranging from 128 vectors and 512 samples per vector to more than 256 vectors and 1024 samples per vector. For an image size of 330 vectors and 512 samples per vector, it can process 30 frames per second using a 300-MHz MAP-CA mediaprocessor from Hitachi/Equator Technologies. This programmable ultrasound machine will not only offer significant advantages in terms of low cost, portability, scalability, and reduced development time, but also provide a flexible platform for developing and deploying new clinical applications to aid the clinicians and improve the quality of healthcare to patients.